2007
DOI: 10.1177/0010414006291189
|View full text |Cite
|
Sign up to set email alerts
|

Transactional and Participatory Activism in the Emerging European Polity

Abstract: In this article, the authors examine the potential for concerted collective action in the societies that emerged from state socialism in East-Central Europe after 1989. Although scholars have found strong individual-level evidence that protest potential is weaker here than in other parts of the world, the authors question whether individual-level data adequately tap all the dimensions of activism that are relevant to contentious politics. They propose a differentiated model of civil society consisting of (a) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(133 citation statements)
references
References 30 publications
3
126
0
4
Order By: Relevance
“…In addition, CSOs have become more professional in dealing with the state (Petrova and Tarrow, 2007). Despite the new opportunities offered by EU accession, there seems to be an emerging consensus in the literature that its legacy has not been fully positive (Fagan, 2005;Börzel andBuzogány, 2010, Batory andCartwright, 2011).…”
Section: Civil Society Eu Accession and The Emergence Of Developmenmentioning
confidence: 99%
“…In addition, CSOs have become more professional in dealing with the state (Petrova and Tarrow, 2007). Despite the new opportunities offered by EU accession, there seems to be an emerging consensus in the literature that its legacy has not been fully positive (Fagan, 2005;Börzel andBuzogány, 2010, Batory andCartwright, 2011).…”
Section: Civil Society Eu Accession and The Emergence Of Developmenmentioning
confidence: 99%
“…As a consequence professional advocacy groups and think tanks and not political parties or loosely organized social movement organizations turned out to be the major actors. The environmental groups of the '90s are the bearers of the so-called transactional activism (Petrova and Tarrow, 2007 The real change for the green, or in a broader sense for the radical left-libertarian movement, came with the new millennium. The protests in Seattle, Genoa, and Prague against the international economic regimes and neoliberal globalization made the global justice movement visible to the global public.…”
Section: Mikecz D: Changing Movements Evolving Parties: the Party-mentioning
confidence: 99%
“…Many studies have reported low levels of societal engagement in the post-communist countries of Central and Eastern Europe (CEE) (Howard 2003). Conversely, other scholars have argued that low levels of civic participation are compensated by activism aimed at connecting with political actors (Foa and Ekiert 2017;Petrova and Tarrow 2006).…”
Section: Introductionmentioning
confidence: 99%